A Blockchain Security Based IoT-Enabled System for Safe and Effective Logistics Management in IR 4.0 - Sarika Agarwal, K. Vinaya Laxmi, Nirmal Kumar Gupta, Mahesh P. Wankhade, Varsha Bapat (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As a result of the revolution brought on by industrial 4.0, the global logistics industry is growing at a rapid rate. Concurrently, logistics operations are undergoing constant change as new technologies such as the internet of things (IoT), cloud computing, and big data are implemented. These Internet of Things devices enhance the functionality of the logistics function by enhancing real-time product tracking, improving data collection, and intelligently storing logistics data, among other things. Because of the centralised database structure of these logistics systems, certain of these new technologies open the door to the possibility of cyberattacks on these systems. The parties involved in the logistics operations must communicate with one another in order to share confidential information about customers and details about products. This is due to the fact that so many logistics stakeholders are being engaged in the process. It is vulnerable to unauthorised access, which may result in fraudulent activity or the production of counterfeit goods by a malicious actor operating within the system. All of these challenges are significant because maintaining the integrity of the logistics data is essential to providing good service to customers. The application of Blockchain’s special features, such as immutability, efficient cryptography, and a distributed decentralised storage system, will be used to address these challenges once it is deployed as an innovation. In conclusion, Blockchain has the potential to improve operational efficiency while also ensuring the safety of the data involved in the logistics process. According to the findings of the study, the technologies underlying Industry 4.0 have the potential to make supply chains more agile, transparent, and resilient. In addition, the study demonstrates that despite the fact that the advantages of integrating technologies related to Industry 4.0 into supply chains are widely acknowledged, there is still a dearth of applications, related research, and actual-world use cases. Nevertheless, it is abundantly clear that companies that do not adopt the technologies will eventually go out of business. In the event that the pandemic has revealed bottlenecks in the practises we use for our supply chain, the solution is to integrate advanced technologies from Industry 4.0.